IsoPSA® Reduces Provider Recommendations for Biopsy and Magnetic Resonance Imaging in Men with Total Prostate Specific Antigen ≥4 ng/ml: A Real-World Observational Clinical Utility Study. Issue 2 (20th March 2022) - Scovell, Jason M.; Hettel, Daniel; Abouassaly, Robert; Almassi, Nima; Berglund, Ryan; Breaux, Todd; Weight, Christopher; Isac, Wahib; Zampini, Anna; Stark, Elizabeth; Rochelle, Robert; Kestranek, Aimee; et al.
Abstract: Introduction: We assessed the impact of the IsoPSA ® test for prostate cancer risk assessment on provider patient management decisions in a real-world clinical setting. Methods: A total of 38 providers, including advanced practice providers, fellowship trained oncologists and general urologists in the Cleveland Clinic health system including both community-based practices and academic locations, enrolled 900 men being evaluated for prostate cancer; 734 met inclusion criteria (age ≥50 years, total serum prostate specific antigen [PSA] ≥4 and <100 ng/ml and no history of prostate cancer) and IsoPSA indication for use. A standard template was used to document biopsy recommendation prior to and after receiving IsoPSA results. The primary outcome was the number of biopsy and magnetic resonance imaging recommendation changes occurring after IsoPSA testing. Results: IsoPSA testing resulted in a 55% (284 vs 638) net reduction in recommendations for prostate biopsy for men with total PSA ≥4 ng/ml. Additionally, a 9% reduction in recommendations for magnetic resonance imaging was observed. There was strong concordance between IsoPSA results and provider recommendations for prostate biopsy, with 87% of patients with an IsoPSA index above the threshold recommended for biopsy and 92% of patients with an IsoPSA index below the threshold not recommended for biopsy. Conclusions: In a real-world clinical setting, providers from diverse training backgrounds and practice settings readily adopted IsoPSA with substantial reductions in the rate of recommended prostate biopsies in patients with elevated PSA values (≥4 ng/ml). There was a high concordance between recommendation for or against prostate biopsy and the IsoPSA result.